Deskripsi Tingkat Motivasi Belajar Siswa pada Proses Transisi Pembelajaran di masa New Normal - Amursalim, Amursalim; Idris, Siti Indriyati; Addas, Reski Kartini (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Motivation is very important for students in the learning process at school because motivation is one of the factors that determine learning outcomes. The students have passed the online learning process, which has transitioned to offline learning now. Contradictory learning conditions certainly affect the level of learning motivation which owned by the students, whether it remains or changes. By this research, the researchers aimed to measure the level of learning motivation which owned during following learning activities that the entire learning process becoming an offline process in this transition process in the academic year of 2022/2023. The entire learning process becoming an offline learning. This research was conducted from October to November 2022 at SMKN Pariwisata Mamasa, West Sulawesi. The type of this research is survey research with a quantitative-descriptive design. The sample was obtained by using the saturated sampling technique, in which the number of samples is equal to the total number of people in the population is 64 which consist of 18 men and 46 women. The research instrument used a motivational questionnaire which consist of 22 statements, 11 of were positive and 11 were negative. The results of this research shows that the average level of student learning motivation in the learning process is in the high category. The aspect that has highest percentage is having hopes and dreams for the future. Meanwhile, the aspect that has lowest percentage is having encouragement and needs in learning.